2020
DOI: 10.1002/ijgo.13287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of the COVID‐19 pandemic on the physical and mental well‐being of obstetricians and gynecologists in Turkey

Abstract: Objective To apply online surveying to assess the general physical and mental well‐being of obstetricians/gynecologists (OB/GYNs) working in COVID‐19 designated hospitals in Turkey. Methods A prospective survey‐based study using an online survey platform. Three hundred participants working at COVID‐19 designated hospitals in Turkey identified from a hospital database were sent a link to the survey by email between April 29 and May 20, 2020. Results A total of 253 OB/GYNs (31 consultants and 222 residents) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
5
18
0
Order By: Relevance
“…These services must also be supplemented by pregnancy counseling services, which improve the mental health of pregnant women [ 22 ]. In addition, psychological support needs to be provided by the family, especially by their partners [ 23 ], which can provide a feeling of comfort for pregnant women [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These services must also be supplemented by pregnancy counseling services, which improve the mental health of pregnant women [ 22 ]. In addition, psychological support needs to be provided by the family, especially by their partners [ 23 ], which can provide a feeling of comfort for pregnant women [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We see that you have overlooked this topic. Although there were 9 original articles [3][4][5][6][7][8][9][10][11] from Turkey indexed in LitCovid between the dates specified in your study, we haven't seen any article about this topic among the selected articles. The study held in our hospital, namely Evaluation of the effect of COVID-19 pandemic on anxiety severity of physicians working in the internal medicine department of a tertiary care hospital: a crosssectional survey yielded that particularly female doctors and physicians who have elderly family members and family members with chronic medical conditions showed more severe symptoms of anxiety [3].…”
Section: Two Separate and Important Points That Should Not Be Forgottmentioning
confidence: 99%
“…One of their greatest fears was giving the virus to family members. Several surveys and reports found that staff members isolated themselves from their families to prevent contagion [19,53]. The British study 'Impact of COVID-19 on the nursing and midwifery workforce' (ICON), which was mentioned in an editorial [62], also noted how afraid nurses and midwives were of infecting family members.…”
Section: Main Topic: Subjective Effectsmentioning
confidence: 99%